Unpolicing the Urban Poor: Consequences of Third-Party Policing for Inner-City Women. (February 2013) - Desmond, Matthew; Valdez, Nicol
Recent decades have witnessed a double movement within the field of crime control characterized by the prison boom and intensive policing, on the one hand, and widespread implementation of new approaches that assign policing responsibilities to non-police actors, on the other. The latter development has been accomplished by expansion of third-party policing policies; nuisance property ordinances, which sanction landlords for their tenants' behavior, are among the most popular. This study, an analysis of every nuisance citation distributed in Milwaukee over a two-year period, is among the first to evaluate empirically the impact of coercive third-party policing on the urban poor. Properties in black neighborhoods disproportionately received citations, and those located in more integrated black neighborhoods had the highest likelihood of being deemed nuisances. Nearly a third of all citations were generated by domestic violence; most property owners abated this "nuisance" by evicting battered women. Landlords also took steps to discourage tenants from calling 911; overrepresented among callers, women were disproportionately affected by these measures. By looking beyond traditional policing, this study reveals previously unforeseen consequences of new crime control strategies for women from inner-city neighborhoods.